A TEACHERS’ SURVEY ON PORTRAYAL OF SEXISM IN THE IMAGES OF IRANIAN EFL SCHOOL TEXTBOOKS - Vahdatinejad, Shapour (PEOPLE: International Journal of Social Sciences, 2018)
The current study was an attempt to investigate the Iranian English as a Foreign Language (EFL) teachers’ opinion on sexism in the images of the Iranian EFL school textbooks. In order to achieve these objectives, 40 (20 male and 20 female) EFL teachers from junior high and high schools in Tehran participated in this study. The data was obtained using a questionnaire which was previously piloted. Findings indicate that all of the teachers are aware of sexism in the images of the current EFL school textbooks and also believe that the books do not represent both genders equally. The findings also show that the teachers detest sexism in the images and would like to eradicate it from textbooks. In addition, the participants believe that textbooks need to be revised to represent both genders equally. According to the results of the current study, the teachers are aware of what actually happens in the educational contexts and they all believe that this type of sexism in the textbooks can have negative effects on students’ behavior toward the other gender in the society. They also highlighted that sexism in the images may impact students future decisions on the study field or their choice of profession. The implications of the study are for the EFL policy makers and textbook writers and EFL teachers.